Acrylamide: Thermally Induced Toxicant in Foods and Its Control Measures - Timilsena, Yakindra Prasad; Khanal, Jyotsna Shrestha; Anal, Anil Kumar (Journal of Food Science and Technology Nepal, 2013)
Acrylamide is a thermally induced toxicant present in different processed foods in varying amount. Due to its detrimental effect on human health, it has become a major concern in public health and food safety. Various reports published recently have identified different processing techniques to reduce the level of this compound in the food. This paper aims to review and focuses on the mechanisms of acrylamide formation, the effects of different processing parameters such as pre-frying treatments, pH, temperature, time, types and the amount of raw materials, its toxicity level, and its detection methods in complex food systems. Toxicity levels of acrylamide have been found to be neurotoxic and carcinogenic. Food safety authorities including Codex Alimentarius Commission are in the process of reviewing their standards to fix the limit of acrylamide in processed foods. J. Food Sci. Technol. Nepal, Vol. 6 (19-30), 2010 DOI: http://dx.doi.org/10.3126/jfstn.v6i0.8256